INVENTORY OF MEDICINAL PLANTS AND THEIR UTILISATION BY THE COMMUNITY OF RENGEL SUB-DISTRICT, TUBAN DISTRICT - Klau, Ivan Charles Seran; Ambari, Yani; Sulistiani, Vidia Dwi; Leki, Karol Giovani Battista; Oktadiana, Isma; Negara, Yohanes Adrian Kapri; Lepangkari, Jaka Seprianto (Medical Sains : Jurnal Ilmiah Kefarmasian, 2025)
Plant inventory is an activity aimed at documenting and classifying plant species within a specific area. This study investigated the utilization of traditional medicines in the Lengger District, Tuvan Province, focusing on the types of medicinal plants, their properties, uses, and the specific plant parts employed. A qualitative descriptive method was applied, and data were collected through observations and interviews. The sampling technique followed a snowball sampling approach, where key informants were identified based on predefined criteria, and additional informants were selected through recommendations. The findings revealed that the community in the Lengger District utilizes 54 types of medicinal plants for traditional healing practices. The conclusion of this research is that preserving traditional medicinal knowledge is very important to prevent the loss of information about the benefits and uses of medicinal plants that have been passed down from generation to generation. Further research is needed to reveal the bioactive content, effectiveness, and safety of medicinal plants so that they can be developed into scientifically based therapies. Given the community's dependence on medicinal plants, conservation efforts through sustainable cultivation and protection of natural habitats must be implemented to ensure their availability in the future and maintain ecosystem balance. Keywords: Inventory, Types of medicinal plants, Rengel District, Tuban Regency